STUDI KOPRESIPITASI Zn2+ DAN Co2+ MENGGUNAKAN Al(OH)3 SEBAGAI KOPRESIPITAN - Dewata, Indang (Sainstek : Jurnal Sains dan Teknologi, 2013)
Research of study copresipitation Zn2+ using Al(OH)3 as coprecipitant has been done. This study aims to determine the optimum conditions for coprecipitation of Zn2+ by Al(OH)3, and influence of foreign ions. This study uses variation pH about 5,0 ? 10,0 and 6,0 ? 10,0 for Co2+;  variation of eluent volume about 8,0 ? 14,0; variation of concentrated HNO3 volume about 1,0 ? 5,0; and variation of concentration Cu2+ and Ni2+ about 0,8; 1,2; 1,6; 2,0 and 2,4, respectively. Measurement concentration of Zn2+ using Atomic Absorption Spectroscopy (AAS) with wavelength of  213,9 nm Zn2+for 240,7 nm for Co2+. The result showed the optimum conditions occur at pH about 8, 12 mL of eluent and 1 mL of concentrated HNO3 with the absorption capacity of 0,074 mg/g for Zn2+ and pH about 8, 12 mL of eluent and 1 mL of concentrated HNO3 with the absorption capacity of 0,0905 mg/g for Co2+. Meanwhile, the presence of foreign ions such as Cu2+ has influenced the coprecipitated Zn where concentration of the coprecipitated Zn decreased with increasing the concentration of foreign ions.Keywords:  coprecipitation, coprecipitant Al(OH)3, trace metal,  Zn, Co, AAS